Characterisation of macrophages in healthy and diseased livers in mice: identification of necrotic lesion-associated macrophages - Yang Wang; Dechun Feng; Bin Gao; Bryan Mackowiak; Yukun Guan; Luca Maccioni (eGastroenterology)
Background Healthy livers contain a large number of resident macrophages named Kupffer cells (KCs), which are partially replaced by infiltrating monocyte-derived macrophages (MoMFs) during acute or chronic liver injury. Despite extensive research, understanding macrophage heterogeneity, spatial distribution and interactions with other cells within the liver remains challenging.Methods This study employs sequential multiplex immunofluorescence staining, advanced image analysis and single-cell RNA sequencing (scRNA-seq) analysis to characterise macrophages in both healthy and diseased livers in mice.Results Our data revealed that liver KCs made up more than 80% of total immune cells in healthy mouse livers, while massive amounts of MoMFs infiltrated into the livers after acute and chronic liver injury. KCs were more abundant and larger in Zones 1 and 2 compared with Zone 3 in healthy livers. Zone 1 KCs exhibited higher phagocytic activity than Zone 2/3 KCs and MoMFs. We simultaneously evaluated cell proliferation and apoptosis on one slide and found that proliferation and apoptosis of KCs and MoMFs significantly increased in acutely injured livers. We also performed scRNA-seq to investigate liver macrophage gene expression in naïve and concanavalin A (ConA)-treated mice. MoMF clusters expanded following ConA treatment, while KCs remained stable. Macrophages were divided into distinct subtypes, including C1q+MoMFs, with differential expression of genes like Trem2, Spp1, Fabp5 and Gpnmb. Newly recruited C1q− MoMFs expressed high levels of Lyz and Ccr2, while Itgax (Cd11c)+ MoMFs expressed endothelin converting enzyme 1 (Ece1), a gene encoding ECE1 enzyme that activates endothelin to promote hepatic stellate cell contraction and necrotic lesion resolution. By immunostaining analysis of the proteins encoded by these signature genes, we identified several populations of MoMFs that were mainly located surrounding the necrotic lesion area and expressed various proteins that are involved in dead cell debris clearance.Conclusion We developed a robust framework for studying liver macrophages in vivo, offering insights into their roles in host defence and liver injury/repair. We identified several populations of MoMFs that surround necrotic lesion areas and express proteins that promote dead cell debris clearance. These necrotic lesion-associated macrophages likely play key roles in promoting necrotic lesion resolution.